The international legal level of information security (Journal of Philosophy Culture and Political Science, 2018)
The global nature of information exchange and interaction makes a number of information security issues relevant, creating the need for the world community to create means and international mechanisms to minimize dangerous impacts on society due to the formation and movement of information flows.